Hashtag Activism and Football Tragedy Commemoration: Social Network Analysis In the #100harikanjuruhan Hashtag on Twitter - Bate, Andi Pajolloi; Amrullah, Haekal Fajri (JURNAL KOMUNIKASI INDONESIA, 2024)
This research explores the role of hashtag activism and the 100-day commemoration of the Kanjuruhan tragedy in shaping the structure and dynamics of social relationships on Twitter. The study utilizes social network analysis (SNA) to analyze the social network around the #100harikanjuruhan (100 Days of Kanjuruhan) hashtag and visualize the network model formed through centrality measurements to identify influential accounts in conversations related to the hashtag. The study found that the formed network structure indicates relatively distant actor distances with low connectivity and one-way ties, as well as centralized power with an insignificant distribution. Furthermore, In the social network formed, actors with high degree, betweenness, and eigenvector centralities do not necessarily have high closeness centrality with all other actors in the network. This shows that in a large network, actors with many connections and high levels of intermediation may not necessarily be able to reach all actors quickly, contributing to the limited resonance of this #100HariKanjuruhan movement on Twitter.